Penerapan Metode Saw Untuk Sistem Pendukung Keputusan Mahasiswa Berprestasi Pada Institut XYZ - Yana Mulya Hayri, Dipo; Resad Setyadi (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
Student achievement is one of the important factors in the success of students in the future. Student achievement in higher education is generally measured by the Grade Point Average (GPA). Decision Support System has concept